Jamaica’s Trade in Ethnic Foods and Other Niche Products : The Impact of Food Safety and Plant Health Standards - Henson, Spencer (Washington, DC : World Bank, 2022)
Many of Jamaica's nontraditional agro-food exports face a broad range of competitiveness constraints related to inconsistent raw material production, high post-harvest losses, relatively high cost and limited availability labor, macroeconomic factors, and intensified regional and other competition. Market access problems related to SPS materials have exacerbated and reinforced these constraints, reducing the profitability and raising the risks associated with the conduct of these trades. The resolution of such SPS constraints is necessary, although not sufficient, to restore and improve the competitiveness of Jamaica's nontraditional agro-food exports. The aims of this study are to examine the efficacy of strategies to comply with emerging standards, assess the extent to which SPS measures have impeded the development of Jamaica's nontraditional exports, and review the prevailing level of SPS management capacities within the country and ongoing efforts to strengthen these. The study first describes the magnitude and composition of agricultural and food exports from Jamaica and then assesses the current status of SPS capacity. On these bases, the potential for SPS measures to impede agricultural and food product exports is assessed, drawing on a number of specific cases in which problems have occurred. An overall assessment of the impact of SPS measures is then undertaken, and recommendations made for future action on the part of both the Jamaican government and private sector.